Comparative study of pars plana vitrectomy with or without intravitreal dexamethasone implant for idiopathic epiretinal membrane - Surabhi S Sane (Indian Journal of Ophthalmology, 2020)
Purpose: To investigate if use of adjunctive intravitreal dexamethasone implant during pars plana vitrectomy (PPV) leads to faster visual recovery and reduction of retinal thickness in idiopathic epiretinal membrane (ERM). Methods: In this non-randomized, comparative, interventional study 30 eyes (from 30 patients with idiopathic ERM) were enrolled. In the control group (n = 15), patients underwent 25-G pars plana vitrectomy (PPV) and ERM peeling. In the study group (n = 15), each patient underwent the same procedure as those in the control group, and also received an additional dexamethasone implant. Primary outcome after treatment was mean gain in best corrected visual acuity (BCVA), and secondary outcome was reduction in central retinal thickness (CRT). Data were analyzed using Fisher's exact test, Wilcoxon rank sum test, and two-sample t-test. Results: The mean gain in BCVA (logMAR) from baseline at 1-month follow-up was significantly higher in the study group (median = -0.3, IQR = -0.4, -0.1) than in the control group (median = 0, IQR = -0.1, 0.3; P < 0.008). However, no significant difference in mean gain in BCVA between the two groups was detectable at the 6-month follow-up (P < 0.55). At 1-month follow-up, one and seven patients in the control and study groups gained ≥15 letters of BCVA (P < 0.05), respectively. The mean reductions in CRT at the 1-month follow-up were significantly higher in the study group than in the control group (Mean = -60 μm, SD = 92.1; P < 0.014; 95% CI = 19.75–156.54). The difference in mean reduction of CRT at 6 months was not significant (P < 0.24). Conclusion: Adjunctive dexamethasone implant can aid faster visual recovery after PPV in idiopathic ERM, although the implants do not affect long-term gains in visual acuity.